Marketing Strategies and Artificial Intelligence - ربيعة بوزيدي (International Journal of Social Communication, 2025)
This study aims to find out the areas of benefit that marketing strategies can achieve from artificial intelligence, and how this innovation with its technologies and applications positively affects the development of marketing mix elements 4p ‘s (product, price, distribution-place-, promotion) which are among the basic pillars for building a feasible and effective marketing strategy. The outputs of artificial intelligence and its effects on the marketing mix ,depend on this point, but the process of analyzing big data extends frequently to reach accurate knowledge of customers’ needs, and allocate products that are in line with their preferences, in order to preserve their loyalty and continue to revive the life cycle of artificial intelligence ,that seeks to update information in a way that contributes to developing the relationship of the elements of the marketing mix with each other and to strengthen the marketing strategy in particular.